Simultaneous Detection of Parasitic Vector Borne Diseases: A Robust Cross-Sectional Survey in Hunting, Stray and Sheep Dogs in a Mediterranean Area - Gizzarelli, Manuela; Foglia Manzillo, Valentina; Ciuca, Lavinia; Morgoglione, Maria Elena; El Houda Ben Fayala, Nour; Cringoli, Giuseppe; Oliva, Gaetano; Rinaldi, Laura; Maurelli, Maria Paola (Frontiers in Veterinary Science, 2019)
Canine vector-borne diseases (CVBDs) are a spectrum of diseases caused by different pathogens transmitted by blood-feeding arthropoda. The aim of this study was to investigate leishmaniosis, babesiosis and filarial infections in dogs with three different lifestyles (hunting, stray and sheep dogs) in Molise, the small region of southern Italy, where data available about these parasitic infections are very scant. A cross-sectional survey was conducted on 318 hunting, 180 stray and 218 sheep dogs. Immunofluorescence antibody test, blood smear, molecular techniques and Knott test were performed to detect Leishmania infantum, Babesia spp. and filarial nematodes. Association between positivity to CVBDs, age, sex and living conditions was evaluated. An overall prevalence of 12.3% of CVBDs caused by L. infantum (10.2%), B. canis canis (0.3%) and filarial nematodes (2.1%) was detected. Three dogs showed co-infections of L. infantum and B. c. canis (0.1%) or Acanthocheilonema reconditum (0.3%). A significantly association was found only for filarial infection in hunting dogs. These parasites were reported also in dogs without clinical signs. It is very important to plan effective control programs for CVBDs to guarantee not only the health and welfare of pets, but also the public safety, because some of mentioned parasites are of zoonotic importance.